Aspirin desensitization in aspirin-exacerbated respiratory disease: New insights into the molecular mechanisms. (October 2018) - Bobolea, Irina; del Pozo, Victoria; Sanz, Veronica; Cabañas, Rosario; Fiandor, Ana; Alfonso-Carrillo, Carolina; Salcedo, María Ángeles; Heredia Revuelto, Rocío; Quirce, Santiago
Abstract: Background: Aspirin desensitization (AD) has been the only available modifying treatment in aspirin-exacerbated respiratory disease (AERD). The mechanisms of AD are nonetheless poorly understood. Though very effective, AD is limited by its risks and side-effects. Objective: Moving forward to the targeted biologicals era, the aim of this study was to characterize the airway inflammatory response to long-term AD, including TSLP dynamics, in order to assess potential new targets in AERD. Patients and methods: Adult patients with aspirin challenge-confirmed AERD underwent an oral AD followed by daily ingestion of aspirin for at least 6 months. Clinical data and inflammatory biomarkers were measured and compared, before and after AD. Induced sputum analyses were performed at baseline, one and six months after AD (differential cell count and levels of sputum supernatant leukotriene C4, prostaglandin D2 and E2, and TSLP). Results: AD was followed by significant clinical improvement, as quantified by all monitored parameters. The good clinical outcomes of AD in our study are supported by overall changes observed in the arachidonic acid metabolites (decreased PGD2 over a constant LTC4/PGE2). TSLP increased (mean baseline 0.1 ± 0.03; 1 month 3.68 ± 7; 6 months 212.2 ± 44 pg/ml; p < 0.01). Conclusions: Our findings suggest that new biologicals blocking TSLP might have a clinical benefit in AERD, by cutting down the TSLP-induced PGD2 generation. Highlights: Though very effective, Aspirin desensitization is limited by its risks and side-effects. This paper improves current knowledge on PGD2-TSLP mechanism involved in aspirin desensitization. Our findings suggest that new drugs blocking TSLP or PGD2 might be effective in AERD.